Avaliação dos riscos de contaminação do solo por agroquímicos em áreas de horticultura na porção Oeste de Boa Vista - RR - Santos, Neila Régea Ervilha (2015)
The city of Boa Vista, capital of the State of Roraima, is located in an area of vegetation of the type Savannas, inserted in an area of soft relief, with a dense water supply and domain of Oxisol. The urban expansion of the city was observed mainly at your section west, where it was intensified the production of vegetables, through a conventional system with the use of chemical products. The objective of this research was to evaluate the risk of contamination of the soil for agrochemicals, in horticulture areas in the District of Operário, located in the portion west of the city. For so much, bibliographical risings, field works and laboratory were accomplished. In field, they happened photographic registrations, collection of points in GPS, opening of six trenches for analysis of soil profiles and collection of samples, besides analysis of two profiles in barrages of tanks of fish and two profiles in walls of pluvial drainage, with collection of 29 soil samples. The Laboratory of Computer Science of the Program of Pós-Graduation in Geography - PPGGEO, of the Federal University of Roraima (UFRR) it was used for the processing of the digital data, through softwares ArcGis 10.0, Spring 5.2 and PCI Geomatics, with the elaboration of location maps, hypsometry, steepness and drainage, using satellite image (LandSat 8) and image TOPODATA (SRTM). The grain size/texture analyses were accomplished at the Laboratory of Sedimentology of the Nucleus of Energy Researches (NUPENERG) of UFRR; the morphology of the grains was made at the Laboratory of Degraded Areas (UFRR). For the pH analyses (hipogenionic potencial) and M.O.S (organic matter of the soil), the samples were directed to the Laboratory of Soils of EMBRAPA Amazonian Oriental of Belém-shovel. The mineralogical analyses happened at the Laboratory of Diffratometry of Raios X of the Department of Physics of UFRR. The results of the analyses of grain size/texture and of morphology of the grains they revealed that the soils of the study area are sandy, with prevalence of the fraction it sands fine with angular and subangular morphology. The pH analyses and M.S.O. they showed that the soils are acid and poor in organic matter. The hypsometry maps and steepness confirmed for the area the domain of soft relief. For the drainage map it was possible to observe that the area of vegetable gardens of the District of Operário is close to a dense water supply. Like this, such results show the need of actions that they seek a better handling of the soil, tends as objective the maintenance of the environmental balance.